Super wear-resistant concrete and preparation process thereof
By using double bond silane coupling agent and polyvinyl alcohol aqueous solution in aluminate cement concrete, the problem of insufficient wear resistance of aluminate cement concrete is solved, and a higher Wear resistance and compactness, suitable for emergency repair projects.
Patent Information
- Application Number
- CN202411526216.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The crystal transformation of existing aluminate cement concrete during hydration results in a reduced wear resistance, and the surface is prone to wear, making it difficult to meet the needs of emergency restoration projects.
Modified by a silane coupling agent with double bonds, a silane modified water reducer is prepared by copolymerizing with methylallyl polyoxyethylene ether and acrylic acid, and mixed steel fibers and nano-aluminum-silicon alloys with polyvinyl alcohol aqueous solution. Powder preparation of modified composite additives, combined with aluminate cement, aggregate and other components to form ultra-wear-resistant concrete.
It significantly improves the wear resistance of concrete, reduces crystal form transformation, enhances density and wear resistance, and is suitable for emergency restoration projects.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to super wear-resistant concrete and a preparation process thereof. Background Art
[0002] As a very commonly used building material, concrete is mainly composed of cementitious materials, aggregates, deionized water, water reducing agents and other components. Among them, the current cementitious materials are mostly cement-based. If the types of cement are classified, concrete can be roughly divided into silicate cement concrete and aluminate cement concrete. Compared with silicate cement concrete, aluminate cement concrete has the advantages of high early strength and excellent corrosion resistance. It is often used in emergency repair projects, such as road repairs. However, the existing aluminate cement concrete still has certain disadvantages that limit its actual application effect. This is because on the one hand, aluminate cement will inevitably face a crystal transformation during the hydration process, that is, CAH. 10 , the C2AH8 crystal form is transformed into the C3AH6 crystal form, and this crystal transformation process will be accompanied by problems such as increased porosity, decreased bonding strength, and volume shrinkage within the system. Ultimately, the wear resistance of aluminate cement concrete is greatly reduced. On the other hand, even if the problem of crystal transformation of aluminate cement is solved, the wear resistance of aluminate cement concrete is still very limited. Its surface is prone to abrasive wear after long-term friction, and microcracks will occur in severe cases, leading to fracture. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a super wear-resistant concrete and a preparation process thereof. The present invention creatively uses a silane coupling agent with a double bond as a modifier, and first hydrolyzes and polycondenses it, and then copolymerizes it with methyl allyl polyoxyethylene ether and acrylic acid based on free radical polymerization, thereby preparing a silane-modified water-reducing agent containing a silanol bond, and then uses a polyvinyl alcohol aqueous solution to sequentially mix, filter, and dry steel fibers and nano-aluminum-silicon alloy powders, thereby preparing a modified composite auxiliary agent with polyvinyl alcohol attached to the surface, and finally, by sequentially adding the silane-modified water-reducing agent and aluminate cement into deionized water for mixing, and then sequentially adding the modified composite auxiliary agent, coarse aggregate, fine aggregate, fly ash and mineral powder for mixing, a concrete with excellent wear resistance and very good market application prospects is prepared.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] The invention discloses a super wear-resistant concrete, which is prepared from deionized water, a silane-modified water-reducing agent, aluminate cement, a modified composite auxiliary agent, a coarse aggregate, a fine aggregate, fly ash and mineral powder.
[0006] As a preferred technical solution of the present invention, the mass ratio of the deionized water, the silane-modified water-reducing agent, the aluminate cement, the modified composite additive, the coarse aggregate, the fine aggregate, the fly ash and the mineral powder is 30:1.5:150:10-12:350-400:180:25-30:15.
[0007] As a preferred technical solution of the present invention, the silane-modified water-reducing agent is prepared by the following steps:
[0008] Step Y1: adding 3-4 parts by weight of methyl allyl polyoxyethylene ether and a double bond silane coupling agent to 100 parts by weight of deionized water, and then stirring and mixing at room temperature for 15-20 minutes to obtain component A;
[0009] Step Y2: Add acrylic acid, mercaptopropionic acid and ascorbic acid to 18-20 parts by weight of deionized water, and then stir and mix at room temperature for 5-10 minutes to obtain component B;
[0010] Step Y3: adding ammonium persulfate to 10-15 parts by weight of deionized water, and then stirring for 5-10 minutes at room temperature to obtain component C;
[0011] Step Y4: Add the component B and the component C dropwise to the component A at 40-50° C. under a nitrogen atmosphere while stirring. After all the additions are completed, continue stirring at a constant temperature for 30-45 minutes to obtain component D;
[0012] Step Y5: adjusting the pH of the component D to 5.5-6 using a sodium hydroxide solution, then performing ultrafiltration using an ultrafiltration membrane, taking the retentate, and finally vacuum drying at 30-40° C. until constant weight, and the preparation is completed;
[0013] The molar ratio of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid is 1:0.4:3-4; the amount of the mercaptopropionic acid is 0.8-1% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the amount of the ammonium persulfate is 4% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the molar ratio of the ascorbic acid to the ammonium persulfate is 1:1.4-1.5.
[0014] Furthermore, the double bond silane coupling agent in step Y1 is one of vinyl trimethoxy silane, vinyl triethoxy silane and γ-methacryloxypropyl trimethoxy silane.
[0015] Furthermore, the dripping of the component B and the component C in step Y4 refers to controlling the dripping rate of the component B to be 1-2 drops / s and the dripping rate of the component C to be 1-2 drops / s.
[0016] Furthermore, the mass fraction of the sodium hydroxide solution in step Y5 is 25-30%.
[0017] Furthermore, the molecular weight cutoff of the ultrafiltration membrane in step Y5 is 3000.
[0018] As a preferred technical solution of the present invention, the modified composite auxiliary agent is prepared by the following steps:
[0019] Step Z1: Mix the polyvinyl alcohol aqueous solution, steel fiber and nano aluminum silicon alloy powder in a mass ratio of 100:2:0.2-0.3 at room temperature for 20-24 hours, then filter, take the filter residue, and finally vacuum dry at 30-35°C until constant weight, and the preparation is completed.
[0020] Furthermore, in step Z1, the mass fraction of the polyvinyl alcohol aqueous solution is 10-12%; and the solute of the polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788.
[0021] A preparation process of super wear-resistant concrete, the preparation process comprising the following steps:
[0022] Step X1: Add silane modified water reducer and aluminate cement to deionized water in sequence, then stir and mix at room temperature for 3-5 minutes, then add modified composite additive, coarse aggregate, fine aggregate, fly ash and mineral powder in sequence, continue to stir and mix at room temperature for 3-5 minutes, and the preparation is completed.
[0023] Beneficial effects of the present invention:
[0024] (1) The present invention creatively uses a silane coupling agent with a double bond as a modifier, which is first hydrolyzed and polycondensed and then copolymerized with methyl allyl polyoxyethylene ether and acrylic acid based on free radical polymerization, thereby preparing a silane-modified water-reducing agent containing a silanol bond, and then using a polyvinyl alcohol aqueous solution to sequentially mix, filter and dry steel fibers and nano-aluminum-silicon alloy powder to obtain a modified composite auxiliary agent with polyvinyl alcohol attached to the surface. Finally, by sequentially adding the silane-modified water-reducing agent and aluminate cement to deionized water for mixing, and then sequentially adding the modified composite auxiliary agent, coarse aggregate, fine aggregate, fly ash and mineral powder for mixing, a concrete with excellent wear resistance and very good market application prospects is prepared.
[0025] (2) Starting from aluminate cement, the present invention creatively prepares a silane-modified water-reducing agent containing silanol bonds, so that in addition to being able to adhere to the surface of cement particles through electrostatic interaction, it can also combine with cement particles in the form of covalent bonds, thereby further promoting the dispersibility of cement particles, obtaining a better dispersion effect, improving the density of the concrete subsequently prepared, and enhancing the wear resistance. Then, steel fibers with polyvinyl alcohol attached to the surface and nano-aluminum-silicon alloy powder are used as modified composite additives for concrete. On the one hand, the addition of steel fibers can well improve the overall performance of concrete. On the other hand, the nano-aluminum-silicon alloy powder has the characteristics of small size and high aluminum content, so that it can not only play an excellent filling role in concrete, but also effectively weaken and reduce the crystal transformation of aluminate cement. At the same time, after polyvinyl alcohol is attached to the surface of steel fibers and nano-aluminum-silicon alloy powder, a stronger "bonding" interface can be formed between the two, promoting the interface bonding between the two and other components. Finally, through the synergistic effect of the two, the wear resistance of concrete is further enhanced.
[0026] (3) The present invention creatively prepares a silane-modified water-reducing agent and a modified composite additive, and the two are added to concrete to jointly endow the concrete with excellent wear resistance. At the same time, compared with the prior art, the present invention requires that the modified composite additive be added after deionized water, silane-modified water-reducing agent and aluminate cement are mixed in the preparation of concrete. Otherwise, the wear resistance of the final concrete will be reduced. The possible reason is that polyvinyl alcohol with a high hydroxyl content is attached to the surface of the modified composite additive, which is easy to interact with the silane-modified water-reducing agent, thereby causing the silane-modified water-reducing agent to be unable to exert the expected dispersion effect on cement particles.
[0027] (4) When the ultra-wear-resistant concrete prepared by the present invention is actually used, it can be cured according to conventional curing conditions and curing methods, which is very convenient and practical. DETAILED DESCRIPTION
[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0029] The aluminate cement in all embodiments and comparative examples of the present invention is purchased directly from the market, purchased from Zhengzhou Kerui Refractory Materials Co., Ltd., and the grade is CA70; the fly ash is purchased directly from the market, purchased from Dongguan Ruiheng Mineral Products Co., Ltd.; the mineral powder is purchased directly from the market, purchased from Shijiazhuang Mayue Building Materials Co., Ltd., and the grade is S95; the methyl allyl polyoxyethylene ether is purchased directly from the market, purchased from Nantong Runfeng Petrochemical Co., Ltd., model HPEG-2400; the steel fiber is purchased directly from the market, purchased from Chongqing Pinhetai Building Materials Co., Ltd., with a specification of 35*0.8mm and a compressive strength of 400MPa; the nano-aluminum-silicon alloy powder is purchased directly from the market, purchased from Xi'an Qiyue Biotechnology Co., Ltd., with a particle size of 100nm and an Al / Si ratio of 88:12.
[0030] The coarse aggregates are all crushed stones, with continuous grading of 5-31.5mm (in line with the requirements of standard JGJ 52-2006), mud content of 0.45wt%, and crushing value index of 11%; the fine aggregates are all river sand with fineness modulus of 2.7, particle grading of zone II (in line with the requirements of standard JGJ 52-2006), and mud content of 1wt%.
[0031] Example 1
[0032] The invention discloses a super wear-resistant concrete, which is prepared from deionized water, a silane-modified water-reducing agent, aluminate cement, a modified composite auxiliary agent, a coarse aggregate, a fine aggregate, fly ash and mineral powder.
[0033] The mass ratio of the deionized water, the silane-modified water-reducing agent, the aluminate cement, the modified composite additive, the coarse aggregate, the fine aggregate, the fly ash and the mineral powder is 30:1.5:150:10:350:180:25:15.
[0034] The silane-modified water-reducing agent is prepared by the following steps:
[0035] Step Y1: Add 3 parts by weight of methyl allyl polyoxyethylene ether and a double bond silane coupling agent to 100 parts by weight of deionized water, and then stir and mix at room temperature for 15 minutes to obtain component A;
[0036] Step Y2: Add acrylic acid, mercaptopropionic acid and ascorbic acid to 18 parts by weight of deionized water, and then stir and mix at room temperature for 5 minutes to obtain component B;
[0037] Step Y3: Add ammonium persulfate to 10 parts by weight of deionized water, and then stir and mix at room temperature for 5 minutes to obtain component C;
[0038] Step Y4: Add the component B and the component C dropwise to the component A at 40° C. under a nitrogen atmosphere while stirring. After all the additions are completed, continue stirring at a constant temperature for 30 minutes to obtain component D;
[0039] Step Y5: adjusting the pH of the component D to 5.5 using a sodium hydroxide solution, then performing ultrafiltration using an ultrafiltration membrane, taking the retentate, and finally vacuum drying at 30° C. until constant weight, and the preparation is completed;
[0040] The molar ratio of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid is 1:0.4:3; the amount of the mercaptopropionic acid is 0.8% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the amount of the ammonium persulfate is 4% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the molar ratio of the ascorbic acid to the ammonium persulfate is 1:1.4.
[0041] The double bond silane coupling agent in step Y1 is γ-methacryloxypropyltrimethoxysilane.
[0042] The dripping of the component B and the component C in step Y4 refers to controlling the dripping rate of the component B to be 1 drop / s and the dripping rate of the component C to be 1 drop / s.
[0043] The mass fraction of the sodium hydroxide solution in step Y5 is 25%.
[0044] The molecular weight cut-off of the ultrafiltration membrane in step Y5 is 3000.
[0045] The modified composite auxiliary agent is prepared by the following steps:
[0046] Step Z1: Mix the polyvinyl alcohol aqueous solution, steel fiber and nano aluminum silicon alloy powder at a mass ratio of 100:2:0.2 at room temperature for 20 hours, then filter, take the filter residue, and finally vacuum dry at 30° C. until constant weight, and the preparation is completed.
[0047] The mass fraction of the polyvinyl alcohol aqueous solution in step Z1 is 10%; the solute of the polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788.
[0048] A preparation process of super wear-resistant concrete, the preparation process comprising the following steps:
[0049] Step X1: Add silane modified water reducer and aluminate cement to deionized water in sequence, and then stir and mix at room temperature for 3 minutes, then add modified composite additive, coarse aggregate, fine aggregate, fly ash and mineral powder in sequence, and continue to stir and mix at room temperature for 3 minutes, and the preparation is completed.
[0050] Example 2
[0051] The invention discloses a super wear-resistant concrete, which is prepared from deionized water, a silane-modified water-reducing agent, aluminate cement, a modified composite auxiliary agent, a coarse aggregate, a fine aggregate, fly ash and mineral powder.
[0052] The mass ratio of the deionized water, the silane-modified water-reducing agent, the aluminate cement, the modified composite additive, the coarse aggregate, the fine aggregate, the fly ash and the mineral powder is 30:1.5:150:12:400:180:30:15.
[0053] The silane-modified water-reducing agent is prepared by the following steps:
[0054] Step Y1: Add 4 parts by weight of methyl allyl polyoxyethylene ether and a double bond silane coupling agent to 100 parts by weight of deionized water, and then stir and mix at room temperature for 20 minutes to obtain component A;
[0055] Step Y2: Add acrylic acid, mercaptopropionic acid and ascorbic acid to 20 parts by weight of deionized water, and then stir and mix at room temperature for 10 minutes to obtain component B;
[0056] Step Y3: adding ammonium persulfate to 15 parts by weight of deionized water, and then stirring and mixing at room temperature for 10 minutes to obtain component C;
[0057] Step Y4: Add the component B and the component C dropwise to the component A at 50° C. under a nitrogen atmosphere while stirring. After all the additions are completed, continue stirring at a constant temperature for 45 minutes to obtain component D;
[0058] Step Y5: adjusting the pH of the component D to 6 using a sodium hydroxide solution, then performing ultrafiltration using an ultrafiltration membrane, taking the retentate, and finally vacuum drying at 40° C. until constant weight, and the preparation is completed;
[0059] The molar ratio of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid is 1:0.4:4; the amount of the mercaptopropionic acid is 1% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the amount of the ammonium persulfate is 4% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the molar ratio of the ascorbic acid to the ammonium persulfate is 1:1.5.
[0060] The double bond silane coupling agent in step Y1 is γ-methacryloxypropyltrimethoxysilane.
[0061] The dripping of the component B and the component C in step Y4 refers to controlling the dripping rate of the component B to be 2 drops / s and the dripping rate of the component C to be 2 drops / s.
[0062] The mass fraction of the sodium hydroxide solution in step Y5 is 30%.
[0063] The molecular weight cut-off of the ultrafiltration membrane in step Y5 is 3000.
[0064] The modified composite auxiliary agent is prepared by the following steps:
[0065] Step Z1: Mix the polyvinyl alcohol aqueous solution, steel fiber and nano aluminum silicon alloy powder in a mass ratio of 100:2:0.3 at room temperature for 24 hours, then filter, take the filter residue, and finally vacuum dry at 35°C until constant weight, and the preparation is completed.
[0066] The mass fraction of the polyvinyl alcohol aqueous solution in step Z1 is 12%; the solute of the polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788.
[0067] A preparation process of super wear-resistant concrete, the preparation process comprising the following steps:
[0068] Step X1: Add silane modified water reducer and aluminate cement to deionized water in sequence, then stir and mix at room temperature for 5 minutes, then add modified composite additive, coarse aggregate, fine aggregate, fly ash and mineral powder in sequence, continue to stir and mix at room temperature for 5 minutes, and the preparation is completed.
[0069] Example 3
[0070] The invention discloses a super wear-resistant concrete, which is prepared from deionized water, a silane-modified water-reducing agent, aluminate cement, a modified composite auxiliary agent, a coarse aggregate, a fine aggregate, fly ash and mineral powder.
[0071] The mass ratio of the deionized water, the silane-modified water-reducing agent, the aluminate cement, the modified composite additive, the coarse aggregate, the fine aggregate, the fly ash and the mineral powder is 30:1.5:150:11:380:180:27:15.
[0072] The silane-modified water-reducing agent is prepared by the following steps:
[0073] Step Y1: Add 3.5 parts by weight of methyl allyl polyoxyethylene ether and a double bond silane coupling agent to 100 parts by weight of deionized water, and then stir and mix at room temperature for 18 minutes to obtain component A;
[0074] Step Y2: Add acrylic acid, mercaptopropionic acid and ascorbic acid to 19 parts by weight of deionized water, and then stir and mix at room temperature for 8 minutes to obtain component B;
[0075] Step Y3: Add ammonium persulfate to 13 parts by weight of deionized water, and then stir and mix at room temperature for 7 minutes to obtain component C;
[0076] Step Y4: Add the component B and the component C dropwise to the component A at 45° C. under a nitrogen atmosphere while stirring. After all the additions are completed, continue stirring at a constant temperature for 40 minutes to obtain component D;
[0077] Step Y5: adjusting the pH of the component D to 5.8 using a sodium hydroxide solution, then performing ultrafiltration using an ultrafiltration membrane, taking the retentate, and finally vacuum drying at 35° C. until constant weight, and the preparation is completed;
[0078] The molar ratio of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid is 1:0.4:3.5; the amount of the mercaptopropionic acid is 0.9% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the amount of the ammonium persulfate is 4% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the molar ratio of the ascorbic acid to the ammonium persulfate is 1:1.45.
[0079] The double bond silane coupling agent in step Y1 is γ-methacryloxypropyltrimethoxysilane.
[0080] The dripping of the component B and the component C in step Y4 refers to controlling the dripping rate of the component B to be 1.5 drops / s and the dripping rate of the component C to be 1.5 drops / s.
[0081] The mass fraction of the sodium hydroxide solution in step Y5 is 28%.
[0082] The molecular weight cut-off of the ultrafiltration membrane in step Y5 is 3000.
[0083] The modified composite auxiliary agent is prepared by the following steps:
[0084] Step Z1: Mix the polyvinyl alcohol aqueous solution, steel fiber and nano aluminum silicon alloy powder in a mass ratio of 100:2:0.25 at room temperature for 23 hours, then filter, take the filter residue, and finally vacuum dry at 33° C. until constant weight, and the preparation is completed.
[0085] The mass fraction of the polyvinyl alcohol aqueous solution in step Z1 is 11%; the solute of the polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788.
[0086] A preparation process of super wear-resistant concrete, the preparation process comprising the following steps:
[0087] Step X1: Add silane modified water reducer and aluminate cement to deionized water in sequence, and then stir and mix at room temperature for 4 minutes, then add modified composite additive, coarse aggregate, fine aggregate, fly ash and mineral powder in sequence, and continue to stir and mix at room temperature for 4 minutes, and the preparation is completed.
[0088] Comparative Example 1
[0089] On the basis of Example 3, the double bond silane coupling agent in step Y1 was changed to an equimolar amount of acrylic acid, and the rest remained unchanged.
[0090] Comparative Example 2
[0091] On the basis of Example 3, the steel fiber in step Z1 is replaced by nano aluminum-silicon alloy powder of equal weight, and the rest remains unchanged.
[0092] Comparative Example 3
[0093] On the basis of Example 3, the nano aluminum-silicon alloy powder in step Z1 is replaced with steel fiber of equal weight, and the rest remains unchanged.
[0094] Comparative Example 4
[0095] On the basis of Example 3, the polyvinyl alcohol aqueous solution in step Z1 was replaced with an equal weight of deionized water, and the rest remained unchanged.
[0096] Comparative Example 5
[0097] On the basis of Example 3, step X1 is changed to adding silane modified water reducer to deionized water, and then stirring for 4 minutes at room temperature, followed by adding aluminate cement, modified composite additive, coarse aggregate, fine aggregate, fly ash and mineral powder in sequence, and continuing to stir for 4 minutes at room temperature to complete the preparation; the rest remains unchanged.
[0098] Test Example 1
[0099] Wear resistance test:
[0100] The super wear-resistant concrete prepared in Examples 1-3 and Comparative Examples 1-5 were cast and cured in sequence (temperature was 20° C., relative humidity was 95%, and time was 28 days) to obtain test pieces with a size of 150 mm×150 mm×30 mm. The test pieces were then subjected to a wear resistance test according to standard GB / T 16925-1997.
[0101] In addition, the curing time of the specimens obtained above was extended, that is, the specimens obtained above were placed in deionized water at a temperature of 70°C for 180 days (the specimens were completely immersed), then taken out, vacuum dried at room temperature for 24 hours, and finally re-tested for wear resistance according to standard GB / T 16925-1997.
[0102] Table 1. Wear resistance test results
[0103] Abrasion resistance Wear resistance (after extended curing time) Example 1 1.39 1.26 Example 2 1.37 1.23 Example 3 1.42 1.31 Comparative Example 1 1.26 1.12 Comparative Example 2 1.23 1.13 Comparative Example 3 1.30 1.01 Comparative Example 4 1.28 1.13 Comparative Example 5 1.18 1.05
[0104] From the comparison of Test Example 1, Example 3 and Comparative Examples 1-5, it can be seen that the super wear-resistant concrete prepared by the present invention has excellent wear resistance, can effectively weaken and reduce the crystal transformation of aluminate cement, and the wear resistance decreases slowly, which is very practical.
[0105] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A super wear-resistant concrete, characterized in that: The super wear-resistant concrete is prepared from deionized water, silane-modified water-reducing agent, aluminate cement, modified composite additive, coarse aggregate, fine aggregate, fly ash and mineral powder.
2. The super wear-resistant concrete according to claim 1, characterized in that: The mass ratio of the deionized water, the silane-modified water-reducing agent, the aluminate cement, the modified composite additive, the coarse aggregate, the fine aggregate, the fly ash and the mineral powder is 30:1.5:150:10-12:350-400:180:25-30:
15.
3. The super wear-resistant concrete according to claim 1, characterized in that: The silane-modified water-reducing agent is prepared by the following steps: Step Y1: adding 3-4 parts by weight of methyl allyl polyoxyethylene ether and a double bond silane coupling agent to 100 parts by weight of deionized water, and then stirring and mixing at room temperature for 15-20 minutes to obtain component A; Step Y2: Add acrylic acid, mercaptopropionic acid and ascorbic acid to 18-20 parts by weight of deionized water, and then stir and mix at room temperature for 5-10 minutes to obtain component B; Step Y3: adding ammonium persulfate to 10-15 parts by weight of deionized water, and then stirring for 5-10 minutes at room temperature to obtain component C; Step Y4: Add the component B and the component C dropwise to the component A at 40-50° C. under a nitrogen atmosphere while stirring. After all the additions are completed, continue stirring at a constant temperature for 30-45 minutes to obtain component D; Step Y5: adjusting the pH of the component D to 5.5-6 using a sodium hydroxide solution, then performing ultrafiltration using an ultrafiltration membrane, taking the retentate, and finally vacuum drying at 30-40° C. until constant weight, and the preparation is completed; The molar ratio of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid is 1:0.4:3-4; the amount of the mercaptopropionic acid is 0.8-1% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the amount of the ammonium persulfate is 4% of the total molar amount of the methyl allyl polyoxyethylene ether, the double bond silane coupling agent and the acrylic acid; the molar ratio of the ascorbic acid to the ammonium persulfate is 1:1.4-1.
5.
4. The super wear-resistant concrete according to claim 3, characterized in that: The double bond silane coupling agent in step Y1 is one of vinyl trimethoxy silane, vinyl triethoxy silane and γ-methacryloxypropyl trimethoxy silane.
5. The super wear-resistant concrete according to claim 3, characterized in that: The dripping of the component B and the component C in step Y4 refers to controlling the dripping rate of the component B to be 1-2 drops / s and the dripping rate of the component C to be 1-2 drops / s.
6. The super wear-resistant concrete according to claim 3, characterized in that: The mass fraction of the sodium hydroxide solution in step Y5 is 25-30%.
7. The super wear-resistant concrete according to claim 3, characterized in that: The molecular weight cut-off of the ultrafiltration membrane in step Y5 is 3000.
8. The super wear-resistant concrete according to claim 1, characterized in that: The modified composite auxiliary agent is prepared by the following steps: Step Z1: Mix the polyvinyl alcohol aqueous solution, steel fiber and nano aluminum silicon alloy powder in a mass ratio of 100:2:0.2-0.3 at room temperature for 20-24 hours, then filter, take the filter residue, and finally vacuum dry at 30-35°C until constant weight, and the preparation is completed.
9. The super wear-resistant concrete according to claim 8, characterized in that: The mass fraction of the polyvinyl alcohol aqueous solution in step Z1 is 10-12%; the solute of the polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788.
10. A process for preparing the super wear-resistant concrete according to any one of claims 1 to 9, characterized in that: The preparation process comprises the following steps: Step X1: Add silane modified water reducer and aluminate cement to deionized water in sequence, then stir and mix at room temperature for 3-5 minutes, then add modified composite additive, coarse aggregate, fine aggregate, fly ash and mineral powder in sequence, continue to stir and mix at room temperature for 3-5 minutes, and the preparation is completed.
Citation Information
Patent Citations
High-strength wear-resistant mortar and preparation method thereof
CN110845202A
Silane modified polycarboxylate superplasticizer, preparation method thereof, concrete admixture using superplasticizer, and preparation method of concrete admixture
CN111732697A
Ultra-large-volume high-strength low-hydration-heat concrete
CN113372049A
Fiber high-strength recycled concrete
CN116854423A
Repairing material for cement concrete structure
CN1962528A
